Prevalence of Anemia among Women Patients Visiting A Dental Hospital - Jagadheeswari Ramamoorthy1 , Gifrina Jayaraj2 , Geo Mani3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Anemia is the decreased oxygen carrying capacity of the blood due to reduction in the concentration ofHemoglobin or RBC. Anemia has a high prevalence and it is considered as a public health issue affectingdeveloped and developing countries. It occurs most commonly in women and children.Prevalence ofAnemia worldwide suggests the need for substantial improvement in the nutritional status of women.Theaim of the study is to assess the prevalence of Anemia among women patients visiting a Dental hospital.Patient records of a total of 86000 patients who visited the hospital between June 2019 to March 2020 werereviewed and the laboratory values of Hemoglobin levels and RBC count of women patients undergoingcomplete hemogram were collected from the case sheets of . The age, Hb% and RBC values were collected.The collected data was tabulated in Excel. It was then imported to SPSS software. Descriptive statistics wasperformed for the obtained results and comparison between groups were done by using Chi square tests.p<0.05 was considered as statistically significant. The prevalence of Anemia among the total women patientswas 39.1%. Among the 39.1% women who were diagnosed with anemia, it was found to be more prevalentin the women of age group 40-60 years with a frequency of 17.8%. The most commonly observed range ofHaemoglobin is 12-13g/dl with a frequency of 26.6% . 0.6% of women had RBC count less than 3 millioncells/mm3. A significant number of female patients were tested with abnormal results. The most commonage group diagnosed with Anemia are women belonging to 40-60 years of age. Routine hemoglobin testingin Dental practice of population at risk may be beneficial. Screening of Anemia is essential to avoid latediagnosis.